Ascertaining the Quality of Catholic Education Among Schools in the Diocese of Iba - Dr. Riogel L. Santiago (Research Parks Publishers, 2021)
This study evaluated the quality of Catholic education among schools in the Diocese of Iba. The quantitative descriptive survey research design was utilized, and data were obtained through the questionnaire adopted from National Standards and Benchmarks for Effective Catholic Elementary and Secondary Schools, which was answered by 210 respondents selected using the convenient sampling method. Gathered data were encoded and analyzed in SPSS using mean for descriptive data. One-Way ANOVA was used to identify significant variations in the assessment of stakeholders on the quality of Catholic education. Significant findings of the study revealed that majority of the respondentsagreed that the school leaders in ACSDI schools ensure the commitment of the Philosophy, Vision, Mission, Goals, and Objectives (PVMGO) statements to the Catholic identity, that there is a harmonious relationship between the governing body of ACSDI schools and the Bishop marked by mutual trust, close cooperation, continuing dialogue and respect for the legitimate authority of the Bishop, that the curriculum is aligned and rooted in the Catholic standards and values to ensure quality education among students, and the development, and that the development plan of the school requires the school leaders and governing body to ensure that the key strategies are in track to identify, grow and maintain significant funding prospects. It was found out also that there were significant variations in the assessment of stakeholders on the quality of Catholic education across schools in terms of mission and Catholic identity, governance and leadership, academic excellence, and operational vitality. Based on the findings of the study, a comprehensive strategic plan was crafted to assure the quality of Catholic education among schools in the Diocese of Iba.